(512) Lecture Note on Operation Research-Theory of Games مذكرة محاضرة حول بحوث العمليات - نظرية الألعاب - محمد الكفراوي (معهد التخطيط القومي, 2026)
تتناول هذه المذكرة الأسس العلمية لـ "نظرية المباريات" (Game Theory) كأحد أهم أدوات بحوث العمليات في تحليل مواقف الصراع وتضارب المصالح بين متخذي القرار. يستعرض البحث الجذور التاريخية للنظرية وإسهامات العلماء في وضع "نظرية " (Minimax)، مع التركيز على دراسة المباريات الصفرية بين شخصين، حيث يمثل مكسب أحد اللاعبين خسارة مساوية للآخر. وتوضح المذكرة عبر نماذج تطبيقية (مثل استراتيجيات حماية القوافل العسكرية من الهجمات) كيفية استخدام مصفوفة الأرباح لتحديد الخيارات المثلى في ظل عدم اليقين بقرارات الخصم ، كما يخصص الملف حيزاً كبيراً للربط بين نظرية المباريات والبرمجة الخطية، مبيناً كيفية صياغة مشكلات القرار المعقدة في نماذج رياضية يمكن حلها بـ "طريقة السمبلكس". ويشرح البحث مفاهيم الاستراتيجيات "النقية" و"المختلطة" وكيفية الوصول إلى نقطة التوازن (Saddle Point) لضمان تحقيق أفضل النتائج الممكنة، مما يحول عملية اتخاذ القرار من مجرد تقديرات شخصية إلى عملية حسابية دقيقة تهدف لتعظيم المنفعة وتقليل المخاطر في البيئات التنافسية. This paper explores the scientific foundations of Game Theory as a key tool in operations research for analyzing conflict situations and competing interests among decision-makers. It examines the theory's historical roots and the contributions of scholars to the development of Minimax theory, focusing on zero-sum games between two players, where one player's gain is an equal loss for the other. Through applied models (such as strategies for protecting military convoys from attacks), the paper demonstrates how to use a win matrix to identify optimal options under uncertainty regarding the opponent's decisions. It also devotes considerable space to linking Game Theory with linear programming, showing how to formulate complex decision problems into mathematical models that can be solved using the Simplex method. The paper explains the concepts of "pure" and "mixed" strategies and how to reach a Saddle Point to ensure the best possible outcome, thus transforming decision-making from mere subjective estimations into a precise computational process aimed at maximizing benefits and minimizing risks in competitive environments.